Compliance and Risk Management in Human Resources and its relations with organizational culture in startups of the technology sector - Lugoboni, Leonardo Fabris (2023)
Compliance aims to standardize expected behaviors and is related to laws and adherence to rules and organizational culture. It also deals with the standardization of values in a given company, directly associating itself with the Human Resources area. In this sense, compliance practices in the area of human resources and their relationship with the organizational culture in startups in the technology sector located in São Paulo were investigated. Semi-structured interviews were conducted with four technology startups based in São Paulo. This research illustrates the practice of young companies, which tend to be revolutionary and innovative and still bring a different approach from other companies. Startups that have structured compliance areas highlight the importance of the human resources area to develop activities to disseminate rules, review policies, build the code of ethics and disseminate a culture of compliance.